The Influence of Bluff Body Shape Variations on Aerodynamic Characteristics in Flow Around a Cylinder - Christian Jovie Yudhananta; Fitri Wahyuni; James Julian; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Elvi Armadani; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
Fluid flow around an object plays an important role in various fields, including aerodynamics, building design, and transportation. This study examines the effect of three two-dimensional bluff body shapes, including Circular, Square, and Diamond, on the flow pattern, drag and lift coefficients, and vortex shedding characteristics. The methodology used is Computational Fluid Dynamics (CFD) simulation for incompressible flow with a Reynolds number of 100. The results show that variations in geometric shapes significantly affect the shape formation, flow stability, and aerodynamic force response. The three bluff body variations were found to produce fluctuating aerodynamic characteristics due to the influence of the von Kármán vortex phenomenon. In the diamond cylinder variation, it was found to be the configuration with the widest shape, having the highest average drag coefficient value of 1.84, and exhibiting the most significant force amplification, with an average lift coefficient value of 0.36 and a Strouhal number (St) of 0.18. Overall, variations in bluff body shapes significantly affect the flow pattern, Vortex Shedding frequency, and the total aerodynamic force acting on the object